(3eSfO GdTGaYis - (3CHh YHO Gddg eMeO Hf EOQjS Hf GdYHGS Hf YKeGf Hf TGaY ,J (B204 (3g` s ((3eMeO Hf eMeO GdHcQi GdYQjTi GdCUagGfi GdHZOGOi s)
(3ChdgG (B:s
(3CNHQfG CHh RQYI WGgQ Hf eMeO GdebOSi CNHQfG GdEeGe CHh YHO Gddg eMeO Hf EOQjS GdTGaYi Cfg SeY CHG gQjQg jbhd SCd QLd QShd Gddg Udi Gddg Ydjg hSde abGd EfG fQcH GdHMQ hfMed eYfG Gdbdjd ef GdeGA adeG hVFfG Hg YWTfG CafJhVC HeGA GdHMQ abGs
(3BNQgG (B:s
(3jfJgi HcJGH GdhUGjG GdPi de jSeY ef GdTGaYi s
(3GdfSNI HgG MhGTs
(3HChdg hbajI Ydi eOQSI GdeMeOjIs
(3HgG fXGe GdJYbjHIs
(3Ydjg SeGYGJ hbQGAGJ YOjOjI HNW cKjQ ef GdYdeGA s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3GdMOjK h GdeUWdMs